2020
DOI: 10.5582/ddt.2020.01002
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides of a fermented food, natto, suppress sucrose-induced hyperglycemia in an <i>in vivo</i> evaluation system and inhibit glucose uptake by human intestinal cells

Abstract: Natto is a well-known traditional Japanese food produced by fermenting soybeans with Bacillus subtilis var natto. Here we found that the water-soluble viscous fraction of natto inhibits sucroseor glucose-induced hyperglycemia in silkworms. The water-soluble viscous fraction treated with DNase I, RNase A, and proteinase K, followed by phenol extraction also suppressed sucroseinduced hyperglycemia in silkworms. The enzyme-treated polysaccharide fraction of natto inhibits glucose uptake by Caco-2 cells, human int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Combination of nattokinase, aronia, red ginseng, and shiitake mushroom was found to improve glucose metabolism and diminish insulin resistance [ 52 ]. Several randomized crossover studies also showed that breakfast accompanied with natto suppressed blood glucose elevation and improved insulin sensitivity in the early postprandial phase, but this may be attributed to -polyglutamic acid and polysaccharide components contained in the natto [ 53 , 54 , 55 ]. In a word, there is still no direct evidence to identify the antidiabetic effect of nattokinase.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of nattokinase, aronia, red ginseng, and shiitake mushroom was found to improve glucose metabolism and diminish insulin resistance [ 52 ]. Several randomized crossover studies also showed that breakfast accompanied with natto suppressed blood glucose elevation and improved insulin sensitivity in the early postprandial phase, but this may be attributed to -polyglutamic acid and polysaccharide components contained in the natto [ 53 , 54 , 55 ]. In a word, there is still no direct evidence to identify the antidiabetic effect of nattokinase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that natto inhibits glucose uptake by human intestinal cells 71 and that natto inhibits dipeptidyl peptidase IV 21 .…”
Section: Potential Beneficial Effect Of Fermented Soybean Foods On Di...mentioning
confidence: 99%